Phase transition in a system of 1D harmonic oscillators obeying Polychronakos statistics with a complex parameter: Поиск новых сверхтекучих систем - Rovenchak, Andrij (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
For a system of 1D harmonic oscillators obeying Polychronakos statistics with a complex parameters the emergence of a phase transition is reported and temperature dependences of energy and heat capacity are studied in detail. Estimations towards a possibility to check the obtained jumps in the specific heat are made.